ANALISIS PENGARUH KONDISI KERJA, MOTIVASI KERJA, DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI KANTOR WILAYAH DIREKTORAT JENDERAL KEKAYAAN NEGARA RIAU, SUMATERA BARAT, DAN KEPULAUAN RIAU - Hartanto, Hartanto; Hendriani, Susi; Maulida, Yusni (Jurnal Tepak Manajemen Bisnis, 2018)
This research is aims to know and analyze the influence amongs of workcondition (X1), work motivation (X2), work discipline (X3) as independentvariables either partially or simultaneously toward employeeâs work performance(Y) as dependent variable at The Regional Office of Directorate General of StateAsset Management in Riau, Sumatera Barat, and Kepulauan Riau during 2017.Methode of research used is questionnaire with population as 55employees on The Regional Office of Directorate General of State AssetManagement in Riau, Sumatera Barat, and Kepulauan Riau and it has beenselected all as the population. The variables measurement uses Likert ScaleTechnique with weighting scale from 1 to 5. To find out the correlation amongvariables X1, X2, X3 towards Y uses statistical technique of correlation anaysis,simple linear regression and multiple linear regression, and to test thesignificance rate uses F test and t test processed with Statistical Product andService Solution (SPSS).The result of research concludes that there is a significant influence fromeach independent variables toward the dependent variable. From the threeindependent variables, the highest percentage is the work condition (X1) towardsthe variable of employeeâs work performance (Y) as 43,7% as compared with thetwo other independent variables. Then it is recommended to The Regional Officeof Directorate General of State Asset Management in Riau, Sumatera Barat, andKepulauan Riau to pay attention for the work condition by giving completed workcondition and make it better ahead, because work condition significantlyinfluences toward the employeeâs work performance.